Polymer capsules as micro-/nanoreactors for therapeutic applications: Current strategies to control membrane permeability. (October 2017) - Larrañaga, A.; Lomora, M.; Sarasua, J.R.; Palivan, C.G.; Pandit, A.
Abstract: Polymer capsules, fabricated either with the aid of a sacrificial template or via the self-assembly of block copolymers into polymer vesicles (polymersomes), have attracted a great deal of attention for their potential use as micro-/nanoreactors and artificial organelles for therapeutic applications. Compared to other biomedical applications of polymer capsules, such as drug delivery vehicles, where the polymer shell undergoes irreversible disruption/rupture that allows the release of the payload, the polymer shell in polymer micro-/nanoreactors has to maintain mechanical integrity while allowing the selective diffusion of reagents/reaction products. In the present review, strategies that permit precise control of the permeability of the polymer shell while preserving its architecture are documented and critiqued. Together with these strategies, specific examples where these polymer capsules have been employed as micro-/nanoreactors as well as approaches to scale-up and optimize these systems along with future perspectives for therapeutic applications in several degenerative diseases are elucidated.